INCREASING STUDENTS WRITTING SKILL USING NARRATIVE TEXT IN SMA 1 PAITON - Anisa, Firlia Nurul; Tirmidi, Tirmidi; Ikhwan, Heru Nur (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to determine the appropriate implementation of narrative text in SMA 1 Paiton to improve students' writing skills. Classroom action research (CAR) with two cycles of action was used to achieve this goal. Each cycle consisted of four stages: planning, action, observation, and reflection. The subjects were 27 students of grade XI in the academic year 2024/2025. The results showed that students improved in writing after using narrative text-based learning. With a significance value of p 0.05, the average score increased from 52.96 to 87.04. Students also showed increased motivation and confidence in writing, and became better able to organize ideas and use narrative text structures correctly. Therefore, it can be concluded that narrative text learning is proven to be effective in improving students' English writing skills in high school.